Short study of Pattern of pediatric diseases admitted from emergency department of Patan Hospital - Shrestha, Sitaram (Journal of General Practice and Emergency Medicine of Nepal, 2015)
Introduction: Pattern of diseases among admitted children may be the valuable information for any institution. This study was done to analyze the pattern of diseases admitted through emergency department of Patan Hospital.Methods: This was a hospital based, retrospective and descriptive study, which was done in department of general practice and emergency medicine. All children admitted from emergency up to age 14 were included in study.Results: Total 37000 patient were seen in emergency in 2014. Among them 5957 were admitted out of which 881 were children. Maximum patients were admitted in October. Majority of admitted children were on age group one to five years.Female were more than male. Maximum no of patients admitted were due to pneumonia, acute gastroenteritis and febrile convulsionConclusion: Pneumonia was the most common clinical diagnosis getting admitted. Any measures to prevent pneumonia in community level needs to be implemented.